APLIKASI STATISTICAL QUALITY CONTROL DAN SIX SIGMA UNTUK PENGENDALIAN KUALITAS PRODUK TILES PT. AVW YANG - Indra Abadi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
This study aims to know how the application of statistical process control and Six Sigma in order to control the product process tiles. Namely primary data collection methods (surveys and observations) and secondary (internal and external). The data used is quantitative data (ratio). The population of 1,250 sheets per day and a sampling technique that probability sampling (simple random sampling) of 125 sheets per day. Pnelitian method used is cheek sheet, control of variable quality, six sigma, cause-effect diagrams, control charts. The results of the discussion concluded that all the samples had levels of accuracy and precision are high that the control process is running normally. The level of sigma level achieved by 2, where the tiles are defective products amounted to 44.43% or 1,000,000 444 300 pieces per sheet.